Les trefles indigenes des hauts plateaux ethiopiens: Champions des forets de l'interieur - Akundabweni, L.S. (1984)
Presents the dry matter yields of 9 trifolium species fertilized at various P levels on a black clay vertisol (PH6) at ILCA's head quarters near Addis Ababa (elevation 2400m, rainfall 1300 mm).